Fundamentals of public safety networks and critical communications systems : technologies, deployment, and management - Ulema, Mehmet; IEEE Xplore (Online Service); Wiley (Hoboken, New Jersey : Wiley, 2019)
A timely overview of a complete spectrum of technologies specifically designed for public safety communications as well as their deployment as management In our increasingly disaster-prone world, the need to upgrade and better coordinate our public safety networks combined with successful communications is more critical than ever.Fundamentals of Public Safety Networks and Critical Communications Systems fills a gap in the literature by providing a book that reviews a comprehensive set of technologies, from most popular to the most advanced communications technologies that can be applied to public safety networks and mission-critical communications systems. The book explores the technical and economic feasibility, design, application, and sustainable operation management of these vital networks and systems. Written by a noted expert in the field, the book provides extensive coverage of systems, services, end-user devices, and applications of public-safety services and technologies. The author explores the potential for advanced public safety systems, and this comprehensive text covers all aspects of the public safety and critical communications network field. This important book: . Provides an introduction to and discussion of the common characteristics of our critical communications systems. Presents a review of narrowband technologies such as Project 25, TETRA, and DMR as well as the broadband technologies such as the LTE technology. Focuses on the emerging technologies that can be adopted to improve our vital communications systems. Discusses deployment of such technologies, including economics and finance, planning and project management. Provides, in detail, the issues and solutions related to the management of such communications networks. Offers a complete list of standards documents Written for professionals in the industry, academics, and government and regulatory agencies, Fundamentals of Public Safety Networks and Critical Communications Systems offers a review of the most significant safety technologies, explores the application for advanced technologies, and examines the most current research.
Users of Critical Communications Systems -- Characteristics of Critical Communications Systems -- Introduction to Technologies and Standards for Critical Communications -- Project 25 (P25) -- Terrestrial Trunked Radio (Tetra) -- Digital Mobile Radio (DMR) -- Long-Term Evolution (LTE) -- Future Technologies for Critical Communications Systems -- Systems and Applications Used in Critical Communications -- End-User Devices Connected to Critical Communications Systems -- Planning for Deployment and Operations of Critical Communications Systems -- Economic and Financial Considerations for Deploying Critical Communications Systems -- Designing, Implementation, and Integration -- Operations, Administration, and Maintenance of Critical Communications Systems -- Summary and Conclusions -- IEEE Press Series on Networks and Services Management.
Also available in print.
Mode of access: World Wide Web
Description based on online resource; title from digital title page (viewed on January 10, 2019).
Keywords: Emergency communication systems; Public safety; Information networks; Electronic books